Aspirin Repurposing in Folate-Decorated Nanoparticles: Another Way to Target Breast Cancer - Kanwal, Fariha; Ma, Mingming; Rehman, Muhammad Fayyaz ur; Khan, Fahim-ullah; Elizur, Shai E.; Batool, Aima Iram; Wang, Chi Chiu; Tabassum, Tahira; Lu, Changrui; Wang, Yao (Frontiers in Molecular Biosciences, 2022)
Breast cancer affects more than one million women per year worldwide. Through this study, we develop a nanoparticle-based drug delivery system to target breast cancer cells. Aspirin has been found to inhibit thromboembolic diseases with its tumor-preventing activity. As a consequence, it relieves disease symptoms and severity. Here, mesoporous Silica Nanoparticles (MNP) have been used to deliver Aspirin to the tumor location. MNP-based Aspirin in folic acid (F)-conjugated Polydopamine (MNP-Asp-PD-PG-F) vehicles are prepared for targeted breast cancer therapy. The vehicle hinges on MNP altered with polymer polyethylene glycol (PG), polydopamine (PD), and folic acid (F). The delivery vehicle was studied for in vitro drug release, cytotoxicity and breast cancer cell proliferation. Folic Acid-conjugated drug delivery vehicles let MNPs achieve an elevated targeting efficacy, ideal for cancer therapy. It was also observed that compared to free Aspirin, our drug delivery system (MNP-Asp-PD-PG-F) has a higher cytotoxic and antiproliferative effect on breast cancer cells.The drug delivery system can be proposed as a targeted breast cancer therapy that could be further focused on other targeted cancer therapies. Delivering Aspirin by PD-PG-F system on the tumor sites promises the therapeutic potential for breast cancer treatment.